Una separazione e i miscugli attraverso l’arte alla scuola dell’infanzia - Racca, Francesca; Turco, Francesca (Chimica nella Scuola, 2024)
1Stepping into the shoes of young scientists, the students of a homogeneous group in the final year of kindergarten tackled the topics of mechanical separation through centrifugation, and downstream, homogeneous and heterogeneous mixtures through an interdisciplinary approach that intertwined science with art, food education, and civic education.